Production and comparative fuel properties of biodiesel from non-edible oils: Jatropha curcas, Sterculia foetida and Ceiba pentandra - Ong H.C.; Silitonga A.S.; Masjuki H.H.; Mahlia T.M.I.; Chong W.T.; Boosroh M.H. (2023)
Biodiesel production from non-edible vegetable oil is one of the effective ways to overcome the problems associated with energy crisis and environmental issues. The non-edible oils represent potential sources for future energy supply. In this study, the physical and chemical properties of crude Jatropha curcas oil (CJCO), crude Sterculia foetida oil (CSFO) and crude Ceiba pentandra oil (CCPO) and its methyl ester have been studied. The acid values of three oils were found to be 12.78 mg KOH per g, 5.11 mg KOH per g and 11.99 mg KOH per g which required acid-esterification and alkali-transesterification process. Acid value was decreased by esterification process using sulfuric acid anhydrous (H2SO4) as a catalyst and alkaline (NaOH) catalyst transesterification was carried out for the conversion of crude oil to methyl esters. The optimal conditions of FAME yield achieved for those three biodiesel were 96.75%, 97.50% and 97.72% respectively. Furthermore, the fuel properties of J. curcas methyl ester (JCME), S. foetida methyl ester (SFME) and C. pentandra methyl ester (CPME) were determined and evaluated. As a result, those produced biodiesel matched and fulfilled ASTM 6751 and EN 14214 biodiesel standards. Based on the results, JCME, SFME and CPME are potential non-edible feedstock for biodiesel production. 2013 Elsevier Ltd. All rights reserved.